A maternal diet enriched in olive oil regulates matrix metalloproteinases activity in maternal and cord blood and in term placentas from women with gestational diabetes mellitus - Gomez Ribot, Dalmiro Leonardo Antonio (2019)
Matrix metalloproteinases (MMPs) are proteolytic enzymes involved in placental development, but markers of a pro-inflammatory state when produced in excess. Previous studies have established that gestational diabetes mellitus (GDM) induces a pro-inflammatory intrauterine environment. We hypothesized that a diet enriched in olive oil (OO) regulates MMP-2 and MMP-9 activities in placentas and in maternal and cord blood from women with GDM. Fifty control (C) and GDM women were enrolled after signing an informed consent (protocol approved by the Ethics Committee of Hospital Pirovano, Buenos Aires). All of them followed the WHO diet for pregnancy, and a group of GDM women received a 26 mL-OO addition daily from week 24-28 of gestation until delivery (GDMO group). At delivery, placental villous explants and maternal and cord blood were obtained and stored at -80ºC for zymography analysis. Fatty acids (FAs) profile was evaluated in cord blood by GC-FID. MMP-9 activity was increased in the placentas and in maternal blood of the GDM group (133 and 81 % respectively, p<0.05 vs. C), alterations prevented by the diet enriched in OO (p<0.05 vs. GDM). No changes were found in the MMP-2 activity among the three evaluated groups. Regarding cord blood, MMP-9 and MMP-2 activities were both increased in the GDM group compared to C (90 and 21 % respectively, p<0.05 vs. C), increases prevented by the OO addition (p<0.05 vs. GDM). These changes occurred without major changes in fatty acid composition in the cord blood from the three experimental groups. The diet enriched in OO modulates MMP-9 activity in term placentas and in maternal and cord blood, indicating the capability of this diet to module the pro-inflammatory intrauterine environment induced by GDM. The lack of changes in FFA profile in cord blood suggest that the unsaturated fatty acids provided by the diet exert antiinflammatory effects within the placenta and fetal organs, with possible benefits for the offspring’s later life.